A phase II study of oxaliplatin and prednisone for patients with relapsed or refractory marginal zone lymphoma: Consortium for Improving Survival of Lymphoma trial. Issue 6 (2nd June 2016) - Oh, Sung Yong; Kim, Won Seog; Kim, Jin Seok; Chae, Yee Soo; Lee, Gyeong-Won; Eom, Hyeon Seok; Ryoo, Hun Mo; Lee, Suee; Kim, Seok Jin; Yoon, Dok Hyun; Won, Jong Ho; Hong, Junshik; et al.
Abstract: Overall, more than 50% of marginal zone lymphoma (MZL) patients experience a relapse within 10 years. This phase II trial was conductedto assess the efficacy and safety of oxaliplatin-prednisone (Ox-P) chemotherapy for patients with relapsed or refractory MZL. Patients received oxaliplatin 130 mg/m 2 on day 1 and prednisone 100 mg/day on days 1–5 of each cycle. A total of 38 patients were enrolled. The median age of the 34 (16 males, 18 females) evaluated patients was 53 (range = 27–74) years. There were seven complete responses (20.6%) and 15 partial responses (44.1%) (Overall response rate = 64.7%). No treatment-related deaths occurred. The median progression-free survival was 14.2 months (95% CI = 2.1–26.3 months); 3-year overall survival rate was 77.7%. Thus, salvage Ox-P chemotherapy for patients with relapsed or refractory MZL at the stated dosage and schedule showed moderate clinical activity and was considerable in very few selected patients (NCT01068392).